Analisis Kebutuhan Intervensi Konseling Karir melalui Psikodiagnostik Individu - Lestari, Yulian Sri (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
This research is an experimental research with an emphasis on career counseling intervention through Individual Psychodiagnostics. The experimental research took place at the Islamic University of Indonesia, with samples of students. The purpose of the research was to see the personal aspects of the subjects. Data collection was carried out using several methods, including psychological test, Observation, and interviews. The results of the study showed that the subjects had met several competency standards such as analysis, achievement motivation, control and concern for order. Although there are still some abilities that need to be improved such as self-control, cooperation and building relationships.